Sustainable Development Challenges in Central Asia: Empirical Evidence on the CO2-Growth-Energy-Employment Nexus - Kurmanov, Nurlan; Kenzhin, Zhaxat; Aldabergenov, Nur; Satbayeva, Aizhan; Mussabalina, Dinara (International Journal of Energy Economics and Policy, 2025)
The following paper analyzes relationships between CO2 emissions, economic growth, total energy consumption, and employment across five Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) over the period between 1992 and 2022, and uses panel econometric methods to do so. Annual World Bank data has been log-transformed to improve statistical properties and interpret coefficients as elasticities. The empirical strategy includes panel unit root tests (LLC, IPS, ADF-Fisher, PP-Fisher), Pedroni cointegration test, Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL) estimation, Dumitrescu-Hurlin panel Granger causality tests, and Forecast Error Variance Decomposition (FEVD). The results have shown the variables to be first-order integrated and have a long-run equilibrium relationship. The short-term analysis has revealed an economic growth’s unidirectional effect on CO2 emissions, indicating a direct deterioration of the environmental situation against economic activity expansion. The long-term analysis has shown how economic growth, energy use, and employment jointly determine emission dynamics while adjustments occur based on the emissions indicator. The variance decomposition has revealed GDP and energy use to be the key long-term determinants and insignificance of employment’s effect. Recommendations include reducing energy intensity, developing low-carbon energy, diversifying the economy, creating green jobs, and strengthening regional cooperation.